REVIEW ARTICLE: DUKUNGAN SOSIAL DALAM SITUASI PANDEMI COVID 19 - May Dwi Yuri Santoso (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
Social support in the Covid-19 pandemic situation for the general public, patients and medical staff is needed in the form of: appraisal support to solve problems or describe stressors, tangible support for real help to solve problems, self esteem support support views both about themselves and belonging support in one part or group. The purpose of this article review is to review various articles on social support during the Covid-19 pandemic so that it is used as information that social support currently has an important role in the Covid-19 pandemic. The method used is a scientific electronic bibliographic database of English articles published through Research Square with 1,001 articles, Google Scholar with 24,000 articles and Pubmed with 141 articles, then 5 articles are selected. The results of the review of the 5 articles selected stated that social support was positively correlated with self-efficacy for Covid-19 disease and sleep quality, while social support was negatively correlated with anxiety, stress, depression, psychological distress for Covid-19 disease and sexual compulsive symptoms. Social support is very important in the dimensions of health and well-being to improve coping mechanisms and quality of life.